Determinação da Intensidade das Tempestades que atuam no Litoral do Rio Grande do Sul, Brasil - BARLETTA, RODRIGO DO CARMO; CALLIARI, LAURO JÚLIO (Pesquisas em Geociências, 2001)
Waves generated by South Atlantic storms are greatly responsible for the beach and coastal erosion verified at the central coast of Rio Grande do Sul State, Brazil. These beaches are classified as intermediate, according to the morphodynamic approach suggested by the “Australian School of Coastal Geomorphology”. The storm wave regime controls the morphodynamic variability of those sandy beaches. Through the classification proposed by Dolan and Davis (1992). South Atlantic storms were classified and related to meteorological systems, considering corresponding beach responses. Out of the 3 year wave gauge storm data analyzed, 54.4% corresponded to Class I (weak), 23% to class II (moderate), 19.25% to class III (significant), 2.75% to class IV (severe) and for class V (extreme), 1 storm was recorded (0.6%). Coincidently, the proportion of storm class frequencies for the 3 year data of South Atlantic storms showed to be similar to the 42 year data studied by Dolan and Davis (1992) for North Atlantic storms. Such classification has proved to be effective for the southern Brazilian coast. Autumn and winter are the storm periods with greatest intensity, wich associated to maximum spring tides and storm surges generate the erosion cicle at this coast. The inverse process is verified to spring and summer, when the accretion cicle takes place. In addiction to this seasonal behavior trend, a continuous process of erosion without further recovering occurred at Conceição Lighthouse and Lagamarzinho beach locations, at rates of 3,6 meter per year and 1 meter per year respectively. The use of such method made possible quantifying storm intensity and establishing its relationship to seasonal erosion processes taking place in the southern Brazilian beaches.